2018
DOI: 10.1038/s41564-018-0318-0
|View full text |Cite
|
Sign up to set email alerts
|

A multicomponent toxin from Bacillus cereus incites inflammation and shapes host outcome via the NLRP3 inflammasome

Abstract: Host recognition of microbial components is essential in mediating an effective immune response. Cytosolic bacteria must secure entry into the host cytoplasm to facilitate replication, and in doing so, liberating microbial ligands which activate cytosolic innate immune sensors and the inflammasome. Here, we identified a multi-component enterotoxin hemolysin BL (HBL) which

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
95
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 79 publications
5
95
0
Order By: Relevance
“…Stimulation of primary wildtype (WT) bone marrow-derived macrophages (BMDMs) with the supernatant of WT B. cereus led to activation of caspase-1, cleavage of GSDMD, secretion of IL-1β and IL-18, and pyroptosis within 3 h, whereas stimulation of WT BMDMs with the supernatant of an isogenic mutant of B. cereus lacking HBL (ΔHbl B. cereus) did not ( Fig. 1a-d), consistent with our previous findings 31 . However, we were surprised to find that WT BMDMs treated overnight with the supernatant of ΔHbl B. cereus underwent robust activation of caspase-1, cleavage of GSDMD, secretion of IL-1β and IL-18, and induction of cell death ( Fig.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Stimulation of primary wildtype (WT) bone marrow-derived macrophages (BMDMs) with the supernatant of WT B. cereus led to activation of caspase-1, cleavage of GSDMD, secretion of IL-1β and IL-18, and pyroptosis within 3 h, whereas stimulation of WT BMDMs with the supernatant of an isogenic mutant of B. cereus lacking HBL (ΔHbl B. cereus) did not ( Fig. 1a-d), consistent with our previous findings 31 . However, we were surprised to find that WT BMDMs treated overnight with the supernatant of ΔHbl B. cereus underwent robust activation of caspase-1, cleavage of GSDMD, secretion of IL-1β and IL-18, and induction of cell death ( Fig.…”
Section: Resultssupporting
confidence: 91%
“…A non-redundant secreted factor of B. cereus activates NLRP3. We have previously demonstrated that innate immune recognition of Bacillus cereus infection requires inflammasome-mediated sensing of a toxin known as HBL 31 . Stimulation of primary wildtype (WT) bone marrow-derived macrophages (BMDMs) with the supernatant of WT B. cereus led to activation of caspase-1, cleavage of GSDMD, secretion of IL-1β and IL-18, and pyroptosis within 3 h, whereas stimulation of WT BMDMs with the supernatant of an isogenic mutant of B. cereus lacking HBL (ΔHbl B. cereus) did not ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The NCBI reference sequences of Bcp1 and PlyB are NC_024137 and YP_009031336, respectively. In the current study, we have extended our previous work to now provide a more detailed characterization of Bcp1 and PlyB (alone and in combination with PlyG endolysin) as antimicrobial agents to address the now growing threat of B. cereus sensu lato organisms as human pathogens (23)(24)(25)(26)(27). Novel antimicrobial agents with differentiated mechanisms of action are highly desirable in an age of emerging and spreading antibiotic resistance.…”
mentioning
confidence: 89%
“…[22][23][24] The NLRP3 inflammasome has been extensively studied in the past two decades. Several stimuli have been reported to trigger NLRP3 inflammasome activation, including endogenous danger signals like ATP, [4][5][6] ionophores like nigericin, 5 particulate matter such as silica and uric acid crystals, 6 viral infection like influenza A virus (IAV), [25][26][27][28] Gram-positive bacterial infection such as Bacillus cereus, 29 Gram-negative bacterial infection like Citrobacter rodentium and Escherichia coli, [30][31][32] and fungal infection like Candida albicans and Aspergillus fumigatus [33][34][35] (Figure 1). Given the diverse stimuli that can activate the NLRP3 inflammasome, it is unlikely that NLRP3 directly binds to these diverse ligands.…”
mentioning
confidence: 99%